How to prepare for quantitative aptitude for CAT: common admission test & other management exam - Sharma, Arun (Tata McGrw Hill, 2016)
How to prepare for quantitative aptitude for CAT: common admission test & other management exam. / Sharma, Arun. -- New Delhi: Tata McGrw Hill, 2016 510 Sh532e7 7th ed. No. of Copies : 1